Efikasi Diri dan Penyesuaian Diri pada Peserta Didik Kelas VII - Mantyawati, Nina Nadya; Septiningsih, Dyah Siti; Setyawati, Rr; Wulandari, Dyah Astorini (Universitas Muhammadiyah Purwokerto, 2022)
This study investigates the relationship between self-efficacy and self-adjustment among seventh-grade students at SMP N 3 Lakbok in West Java, Indonesia. Employing a quantitative correlational research design, the study involved 175 students as respondents. Data were collected using self-efficacy and self-adjustment scales, with reliability assessed via Cronbach’s Alpha. The validity of the scales was confirmed using the Product Moment correlation technique. The self-efficacy scale included 29 valid items and 11 invalid items, with a reliability coefficient of 0.815. The self-adjustment scale comprised 21 valid items and 19 invalid items, with a reliability coefficient of 0.769. Statistical analysis revealed a significant correlation between self-efficacy and self-adjustment (p = 0.000, p < 0.05), indicating that higher self-efficacy is associated with better self-adjustment among students. Specifically, self-efficacy accounts for 26.5% of the variance in self-adjustment, suggesting that additional 73.5% of factors influencing self-adjustment warrant further investigation. Future research should explore other factors contributing to self-adjustment beyond self-efficacy, such as social support, academic environment, and personal experiences, to develop a more comprehensive understanding of the dynamics affecting student self-adjustment.